Perceived Service quality, Supply Chain Collaboration, Supply Chain management as Antecedents of Loyalty and Customer Satisfaction: Exploring Moderating Role of WOM - Mariana Tenreng; Arifin Idrus; Annas Lalo; Syamsiah Badruddin (International Journal of Supply Chain Management, 2019)
Purpose – The main purpose of the current study is to examine the impact of supply chain management, perceived service quality and collaboration on customers satisfaction and loyalty. Moreover, mediating impact of customer satisfaction among supply chain management, perceived service quality and collaboration and loyalty is examined as well. Analysis approach – For this study we have used the survey-based method for data collection, therefore we prepared a structured questionnaire according to research objectives. Findings – the results show that supply chain collaboration has no significant impact on customer satisfaction. As well WOM and customer loyalty are not significantly related to each other. All the other proposed hypothesis has shown significant results. Research implications – Due to the limited sample size, the estimate and testing of a comprehensive model of the relationships between supply chain practices and customer loyalty are not presented. Practical implications – On managerial level, the study provide high level study regarding supply chain management, collaboration, service quality, customer satisfaction and customer loyalty in the business environments characterized by high supply complexity.